Micellar Catalysis of Chemical Reactions by Mixed Surfactant Systems and Gemini Surfactants - Hassan, Mohammed; M. Al-Hazmi, Sadeq; A. Alhagri, Ibrahim; N. Alhakimi, Ahmed; Dahadha, Adnan; Al-Dhoun, Mohammad; Batineh, Yazan (Asian Journal of Chemistry, 2021)
Micellar catalysis exhibited by mixed surfactant systems and gemini surfactants was reviewed. The review focused on mixed surfactant systems and tried to correlate the changes in the physico-chemical properties of these systems to the variations of their catalytic activities. Mixed surfactant systems are promising as the catalytic efficiency of some single surfactants was significantly enhanced in the presence of other critically selected surfactants. The selection should consider the charge, size, and structures of the head group as well as an appropriate length of hydrocarbon tail. The overall conclusion has arrived the mixed surfactant systems could be a tool by which the reaction rate can be tuned by changing the composition and/or the components’ structures. The higher catalytic activity of gemini surfactants compared to conventional ones, their facile synthesis and liability for structure control made them of superior choice for micellar catalysis.